PENGARUH STATUS HARA KALIUM TANAH TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN NENAS - Safuan, La Ode; Poerwanto, Roedhy; Susila, Anas D; Sobir, Sobir (Jurnal Agroteknos, 2011)
The aims of the research were: 1. to investigate effect of potassium status on pineapple growth and production and N, P, K nutrient uptake , and 2. to determine the critical level of potassium for pineapple. The research was conducted using randomized blocked design with five soil K dosages: Ksr = 0 kg K2O ha-1, Kr = 70 kg K2O ha-1, Km = 140 kg K2O ha-1, Kt = 210 kg K2O ha-1 and Kst = 280 kg K2O ha-1. The plant growth, N, P, K nutrient up take and pineapple production were affected by soil potassium status and dosage of potassium application. The critical level of potassium for pineapple “D ” leaf was 1.71% of dry matter. Key words: Growth, production, nutrient status, potassium.